1991
DOI: 10.1128/jvi.65.6.3131-3139.1991
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cloned chicken anemia virus DNA that contains all elements for the infectious replication cycle

Abstract: Circular double-stranded replication intermediates were identified in low-molecular-weight DNA of cells of the avian leukemia virus-induced lymphoblastoid cell line 1104-X-5 infected with chicken anemia virus (CAV). To characterize the genome of CAV, we cloned linearized CAV DNA into the vector pIC20H. Transfection of the circularized cloned insert into chicken cell lines caused a cytopathogenic effect, which was arrested when a chicken serum with neutralizing antibodies directed against CAV was added. Chicken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
101
0
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(103 citation statements)
references
References 42 publications
1
101
0
1
Order By: Relevance
“…Although important criteria in the characterisation and eventual classification of n e w viruses, genomic size and structure are only t w o of many characteristics which need to be evaluated. There is growing evidence to suggest that PCV and CAV can be further distinguished with regard to genome organization a n d expression (MANKERTZ e t al., 1993;MEEHAN et al, 1992;NOTEBORN et al, 1991NOTEBORN et al, , 1992. These results and the results presented in this paper should contribute to a better understanding of the properties of PCV and CAV a n d aid eventual classification of these viruses.…”
Section: Discussionmentioning
confidence: 54%
“…Although important criteria in the characterisation and eventual classification of n e w viruses, genomic size and structure are only t w o of many characteristics which need to be evaluated. There is growing evidence to suggest that PCV and CAV can be further distinguished with regard to genome organization a n d expression (MANKERTZ e t al., 1993;MEEHAN et al, 1992;NOTEBORN et al, 1991NOTEBORN et al, , 1992. These results and the results presented in this paper should contribute to a better understanding of the properties of PCV and CAV a n d aid eventual classification of these viruses.…”
Section: Discussionmentioning
confidence: 54%
“…TTV resembles most closely the chicken anemia virus (CAV) of the circoviridae family. CAV is highly speci®c for the bone marrow and thymus and can be cultured only in actively proliferating lymphoid and hematopoietic cell lines [Noteborn et al, 1991]. Apart from the liver tropism that has been suggested [Nishizawa et al, 1997;Okamoto et al, 1998], PBMCs and bone marrow hematopoietic cells have been the two suspected sites of TTV replication [Kanda et al, 1999;Okamura et al, 1999;Okamoto et al, 1999a;Kikuchi et al, 2000].…”
Section: Discussionmentioning
confidence: 99%
“…Chen (Chen et al 1986, Cihak et al 1988, Sowder et al 1988); anti-CD8 and anti-CD4, which were gifts from Dr T.F. Davison; CVI-ChT-74.1 (histologically characterized as specific for T cells, Noteborn et al 1991, but shown to react positively with COS cells transfected with CD8 plasmid clone; pers. comm.…”
Section: Antibodiesmentioning
confidence: 99%